Kardiochirurgia dorosłychMitral valve repair using modified chordal replacement - Partyka, Adam; Urbanski, Paul; Przybylski, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: The aim of this study is to evaluate the new technique of chordal replacement, which is based on reverse sequence of polytetrafluoroethylene chordae implantation with their attachment to the margin of the prolapsed leaflet and subsequently to the papillary muscle. This ensures that the ultimate length of the artificial chordae is determined during fixation at the papillary muscle and not during knotting at the leaflet level. An additional advantage of this technique is the possibility of intraoperative chordae length correction without the necessity of their re-replacement. Material and methods: From May 2003 to July 2005, 64 consecutive patients with severe mitral regurgitation due to leaflet prolapse underwent chordal replacement using the technique presented. In echocardiographic evaluation 97% of them had had severe mitral regurgitation. All patients underwent repair with artificial chordae replacement and annuloplasty with mitral Physio Ring. Intraoperative chordae length correction was done in 6 cases (9.37%). Echocardiographic control of the repaired valve was performed during surgery by TEE, then before discharge from the hospital, and lastly during follow-up of 2 to 27 months (13 months ±7.15). Results: Mitral repair was primarily successful in 98.44% of cases. Only one patient needed re-operation in the early postoperative period because of leaflet damage at the site of chordal fixation and underwent successful re-repair. Two patients developed severe mitral regurgitation during the follow-up time and their valves had to be replaced 6 weeks and 10 months after primary surgery. Actuarial freedom from mitral regurgitation 2 years after surgery was 94%. Conclusions: Mitral valve repair with modified technique of chordal replacement is effective, safe and reproducible. The technique allows the primary reaching of appropriate length of the artificial chords with very good functional results during the intermediate follow-up.